A 19th century daily surface pressure series for the Southwestern Cape region of South Africa: 1834–1899. (4th November 2018) - Picas, Jessica; Grab, Stefan; Allan, Rob
Abstract : The first daily mean sea‐level pressure (MSLP) series for the Southwestern Cape region of South Africa is presented for the 19th century, and is one of the longest and oldest for the Southern Hemisphere. Sub‐daily barometer readings from the South African Astronomical Observatory were digitized, together with temperature readings, and extend over the period 1834–1899. Pressure readings were recorded using mercury barometers and so needed to be corrected and reduced to standard conditions. Overall, austral winter (June, July, August) has the highest mean monthly MSLP values, symptomatic of the ridging anticyclones during this season. The year 1862 stands out with particularly low MSLP values and has 27 days during austral winter that were below the 10th percentile. This most likely indicates that the winter of 1862 experienced the highest number of passing cold fronts throughout the 66‐year study period. Abstract : The first daily MSLP series for the Southwestern Cape region of South Africa is presented for the 19th century, and is one of the longest and oldest for the Southern Hemisphere. Sub‐daily barometer readings were digitized from the original hard copies. These barometer observations were corrected to modern‐day standard conditions, reduced to MSLP and an equivalent 24‐hr daily mean was calculated. The year 1862 stands out with particularly low MSLP values and has 27 days during austral winter that were below the 10th percentile, likely indicative of a high number of passing cold fronts.